2008
DOI: 10.1212/01.wnl.0000313834.22171.17
|View full text |Cite|
|
Sign up to set email alerts
|

A 12-week, placebo-controlled study (6002-US-006) of istradefylline in Parkinson disease

Abstract: Istradefylline demonstrated a significant reduction in the percentage of awake time per day spent in the OFF state, which resulted in a clinically meaningful reduction in OFF time, without an increase in ON time with troublesome dyskinesia, and was well tolerated as adjunctive treatment to levodopa in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(99 citation statements)
references
References 15 publications
4
92
0
3
Order By: Relevance
“…In these studies, istradefylline was utilized as add-on therapy to 1500 PD patients with motor fluctuations and dyskinesia. These studies demonstrated a statistically significant, but modest decrease of 0.7-1.2 h 'off ' time, associated with a similar increase in 'on' time (LeWitt et al, 2008;Stacy et al, 2008). The frequency of dyskinesia in the treated group was actually greater than that observed in the group treated with placebo.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 74%
“…In these studies, istradefylline was utilized as add-on therapy to 1500 PD patients with motor fluctuations and dyskinesia. These studies demonstrated a statistically significant, but modest decrease of 0.7-1.2 h 'off ' time, associated with a similar increase in 'on' time (LeWitt et al, 2008;Stacy et al, 2008). The frequency of dyskinesia in the treated group was actually greater than that observed in the group treated with placebo.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 74%
“…Selective A 2A blockers are being evaluated for the treatment of Parkinson's disease and for drug addiction on the basis of these compounds' ability to simulate activation of dopamine D 2 receptors (Svenningsson et al, 1999;Jenner et al, 2009;Pinna, 2009). The selective A 2A antagonists (E)-1,3-diethyl-8-(m,p-dimethoxystyryl)xanthine [KW6002 (43); istradefylline; Kyowa-Hakko Kogyo, Tokyo, Japan] has been extensively studied in large phase III studies (Hauser et al, 2008;LeWitt et al, 2008;Stacy et al, 2008) Investigators at the National Institute on Drug Abuse are conducting An fMRI Study of SYN115 in Cocaine Dependent Subjects (www.clinicaltrials.gov identifier NCT00783276). The dopamine system is critical in modulation of reward and has been implicated in the initiation and maintenance of addiction.…”
Section: Adenosine Receptor Antagonistsmentioning
confidence: 99%
“…Moreover, on the basis of the apparent protective effect of coffee in PD, adenosine receptor (A 2A ) antagonists have also been tested and there is evidence that they improve parkinsonian symptoms in animal models [670] and clinical trials [671][672][673][674]. Lastly, the more recently indicated protective effect of uric acid, together with its ability to slow disease progression, has led to the initiation of a clinical trial of inosine, a precursor that increases uric acid levels.…”
Section: Comments and Perspectivesmentioning
confidence: 99%